2022
DOI: 10.3390/s22103917
|View full text |Cite
|
Sign up to set email alerts
|

GAN-Based Video Denoising with Attention Mechanism for Field-Applicable Pig Detection System

Abstract: Infrared cameras allow non-invasive and 24 h continuous monitoring. Thus, they are widely used in automatic pig monitoring, which is essential to maintain the profitability and sustainability of intensive pig farms. However, in practice, impurities such as insect secretions continuously pollute camera lenses. This causes problems with IR reflections, which can seriously affect pig detection performance. In this study, we propose a noise-robust, real-time pig detection system that can improve accuracy in pig fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The image data used by the system were transmitted at a frame rate of 21 fps from a top-down angle RGB camera installed in the ceiling to minimize occlusions and overlapping with people and other objects. This angle also provides an intuitive way of localizing the objects of interest inside a room and studying their movements, making it commonly used in monitoring systems [ 49 , 50 , 51 , 52 , 56 ]. In this module, the collected RGB images are resized to .…”
Section: Behavior-based Dog Video Summarization Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The image data used by the system were transmitted at a frame rate of 21 fps from a top-down angle RGB camera installed in the ceiling to minimize occlusions and overlapping with people and other objects. This angle also provides an intuitive way of localizing the objects of interest inside a room and studying their movements, making it commonly used in monitoring systems [ 49 , 50 , 51 , 52 , 56 ]. In this module, the collected RGB images are resized to .…”
Section: Behavior-based Dog Video Summarization Systemmentioning
confidence: 99%
“…Owing to recent advances in deep learning, the field of object detection has shown continuous improvements in speed and performance and led to the development of methods and models targeting several areas of research and covering different scenarios [ 57 , 58 ]. Among the existing object detection models, You Only Look Once (YOLO) [ 59 ] and its variants have attracted considerable attention because of their performance and real-time inference speed, making them a popular choice for monitoring systems [ 37 , 56 , 60 , 61 ].…”
Section: Behavior-based Dog Video Summarization Systemmentioning
confidence: 99%
“…Testing the pig object detection under lighter hardware is also considered for overall process speed [ 34 ]. Reducing image noise can increase overall image quality, thus improving the detection accuracy for pig monitoring [ 35 , 36 ]. There are more pig farm images on different pig pen environments like a camera is installed with top-view [ 19 ] or tilted-view [ 21 , 30 ], but facility has not presented.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, managing each pig individually to their health and welfare needs is not an easy task. To reduce management workload, many studies have reported the use of surveillance techniques to address health and welfare problems [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Therefore, the use of object detection [ 37 ] to detect pigs by means of a surveillance camera can reduce the management workload within a pig pen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation